A Chart Review on the Feasibility and Safety of the Vincristine Irinotecan Pazopanib (VIPaz) Association in Children and Adolescents With Resistant or Relapsed Sarcomas - Russo, Ida; Di Paolo, Virginia; Crocoli, Alessandro; Mastronuzzi, Angela; Serra, Annalisa; Di Paolo, Pier Luigi; Di Giannatale, Angela; Miele, Evelina; Milano, Giuseppe Maria (Frontiers in Oncology, 2020)
Background: Pediatric patients with relapsed or refractory sarcomas have poor outcome and need novel therapies that provide disease control while maintaining an acceptable quality of life. The safety of vincristine, irinotecan, and pazopanib (VIPaz) association has not yet been published in this population. Methods: A chart review was conducted in children and adolescents with relapsed or refractory bone and soft tissue sarcomas who received VIPaz in our institution. Results: One hundred sixty-six patients with a diagnosis of soft or bone sarcoma were admitted to our hospital in the period between March 2015 and August 2018, 30 were relapsed or resistant. Seventeen out of 30 resistant or relapsed patients (median age, 14 years) received 114 VIPaz cycles (median six cycles per patient, range 1–17). Sixteen courses (15%) resulted in gastrointestinal toxicity with Grade two diarrhea; 35 courses (30%) resulted in Grade ≥3 neutropenia. One patient presented Grade two hypothyroidism after nine courses, and another one had Grade two hyperbilirubinemia after 12 courses. Two and five patients required a 25% dose reduction of irinotecan (because of diarrhea) and pazopanib (because of neutropenia four and hyperbilirubinemia 1), respectively. No patient experienced heart failure, hypertension, nor posterior reversible encephalopathy syndrome. Pneumothorax was not reported in any case even in lung metastatic patients. After two and four VIPaz cycles, we observed one complete response (CR), five partial responses (PRs), seven stable diseases (SDs), and four progressive diseases (PDs). With a median follow-up of 15 months (range 3–32), five out of 17 (29%) patients were alive, and four patients were in continuous CR after 12 VIPaz cycles. Conclusions: The VIPaz regimen might be a safe option in children and adolescents with relapsed or refractory sarcomas otherwise unable to be enrolled in other clinical trials; on the other hand, the efficacy of pazopanib observed cannot be sustained from the current study.